(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The biochemical composition of three species of Rhodophyta (Laurencia papillosa, Jania rubens and Hypnea musciformis) have been studied. The algal specimens have been collected from Ibn Hani coast north of lattakia in spring 2019. The soluble carbohydrates in L.papillosa, J.rubens and H.musciformis is (21.85%), (23.5%) and (27%) weight/dryweight [w/dw] respectively. The total proteins content is (15%), (9.64%) and (13.2%) [w/dw] respectively. The total lipids content is (3.75%), (1.8%) and (2.89%) [w/dw] respectively.